STRATEGIC HRM PRACTICES AND FIRM PERFORMANCE: THE MODERATING ROLE OF ENVIRONMENTAL DYNAMISM IN BANDUNG - Fitra Nurhakim; Sri Lestari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the effect of Strategic Human Resource Management (SHRM) practices on firm performance and investigates the moderating role of environmental dynamism in firms operating in Bandung. A quantitative approach was employed using a cross-sectional survey of 214 firms. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Measurement and structural models were assessed following established reliability and validity criteria, and moderation analysis was conducted using an interaction term. The results indicate that SHRM practices have a positive and significant effect on firm performance (β = 0.421, p < 0.001). Environmental dynamism also shows a significant positive effect on firm performance (β = 0.276, p < 0.001). Furthermore, environmental dynamism strengthens the relationship between SHRM practices and firm performance (β = 0.198, p < 0.01). The model explains 57.3% of the variance in firm performance (R² = 0.573), indicating moderate explanatory power. This study is limited by its cross-sectional design, reliance on self-reported data, and focus on a single regional context, which may affect generalizability. This study contributes to the literature by integrating the Resource-Based View with contingency and dynamic capability perspectives, highlighting environmental dynamism as a key boundary condition in the SHRM–performance relationship within an emerging market context.